Authentic and Play-Acted Vocal Emotion Expressions Reveal Acoustic Differences - Jürgens, Rebecca; Hammerschmidt, Kurt; Fischer, Julia (Frontiers in Psychology, 2011)
Play-acted emotional expressions are a frequent aspect in our life, ranging from deception to theatre, film and radio drama, to emotion research. To date, however, it remained unclear whether play-acted emotions correspond to spontaneous emotion expressions. To test whether acting influences the vocal expression of emotion, we compared radio sequences of naturally occurring emotions to actors’ portrayals. It was hypothesized that play-acted expressions were performed in a more stereotyped and aroused fashion. Our results demonstrate that speech segments extracted from play-acted and authentic expressions differ in their voice quality. Additionally, the play-acted speech tokens revealed a more variable F0-contour. Despite these differences, the results did not support the hypothesis that the variation was due to changes in arousal. This analysis revealed that differences in perception of play-acted and authentic emotional stimuli reported previously cannot simply be attributed to differences in arousal, but by slight and implicitly perceptible differences in encoding.